Addressing Rational Prescribers through the Pharmacology and Therapeutics Course Work of MBBS Syllabus in Bangladesh - Mainul, Haque; Nor Iza, A.Rahman; Ahmed Ghazi, Faisal (2013)
Pharmacology is most rapidly expanding science in medical discipline which leads to the development of many important drugs to treat many medical conditions that was previously untreatable. This paper focuses on the necessity of integration of pharmacology in the medical curriculum in all clinical phases and ethical aspects of medicine in terms of irrational prescribing. Irrational prescribing of drugs is a major global health problem in medical practice. Currently Pharmacology is taught at phase-II, a 2 year period in a 5 years undergraduate medical Programme in Bangladesh under the name ‘Pharmacology and Therapeutics’. Indiscriminate use of clinically inappropriate and ineffective medicines are a serious problem. Medicines in Bangladesh are inappropriately prescribed, again all kinds of drugs including controlled products are dispensed and sold out frequently without prescription. Henceforth there are regular violation of medical ethics and professionalism. As only pharmacology and therapeutics deals with the correct selection of drugs, the subject should be continued to teach up to phase-III. In addition, therapeutic discussion should be incorporated with proper logbook during internship in order to make safe and efficient prescribers. Supreme priority should be given to legal and ethical aspects of medicine. Medical professionals must uphold social order by ensuring ethical practices of medicine and appropriate role modelling especially by the faculty.